KONSEPTUAL MODEL PENDIDIKAN DEMOKRATIS PERSPEKTIF PENDIDIKAN ISLAM - Irawan Irawan; Denny Hermawan (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2019)
AbstractDemocracy about education in which many problems often occur, one of which is a problem that often occurs in the world of education according to the observations of researchers, such as schools, especially teachers often become a reference of many things that are not desired by the community. When children depend on watching television, it is the school that is targeted because it is considered not to provide maximum media education. When brawls often occur, it is the school that is highlighted the most because schools lack instill education in values. When people do not know much about technology, it is also the school that is the focus because of inattention to the times, and there are still many other examples of problems. The purpose of this study is to find out what is a democratic concept in Islam and to explain democratic education according to Islam. The research method used is a grounded theory method that uses data from materials that are a library (library research), where the author reads and studies books or literature relating to the problem under study. The principles of Islamic democracy towards Islamic education are: There is freedom for educators and students, which freedom here includes: freedom of work, freedom to develop potential and freedom of opinion. Similarities with students in Islamic education. Because Islam provides equal opportunities for all students to get an education or study. Respect for the dignity of individuals in Islamic education. Keywords: Democracy; Discussion; Education; Value.    Abstrak Demokrasi mengenai pendidikan yang mana banyak permasalahan yang sering terjadi salah satunya adalah masalah yang sering terjadi dalam dunia pendidikan menurut hasil pengamatan peneliti, seperti: sekolah terutama guru sering menjadi rujukan dari banyak hal yang tidak diinginkan masyarakat. Ketika anak-anak ketergantungan menonton televisi, sekolahlah yang yang menjadi sasaran karena dianggap tidak memberikan pendidikan media yang maksimal. Ketika sering terjadi tawuran, sekolahlah yang paling disorot karena sekolah kurang menanamkan pendidikan nilai. Ketika masyarakat tidak mengenal jauh teknologi, sekolahlah juga yang menjadi tumpuan karena kurang perhatian terhadap perkembangan zaman, dan masih banyak contoh masalah-masalah yang lainnya. Tujuan dari penelitian ini adalah untuk mengetahui konsep demokratis dalam Islam dan untuk menjelaskan pendidikan demokratis menurut Islam. Metode penelitian yang digunakan adalah metode teori dasar yang menggunakan data dari bahan-bahan yaitu bersifat kepustakaan (library research), dimana penulis membaca dan mempelajari buku-buku atau literatur yang berhubungan dengan permasalahan yang diteliti. Prinsip demokratis dalam Pendidikan Islam yaitu: Adanya kebebasan bagi pendidik dan peserta didik, yang mana kebebasan di sini meliputi: kebebasan berkarya, kebebasan mengembangkan potensi dan kebebasan berpendapat. Persamaan terhadap peserta didik dalam pendidikan Islam. Karena, Islam memberikan kesempatan yang sama bagi semua peserta didik untuk mendapatkan pendidikan atau belajar. Penghormatan akan martabat individu dalam pendidikan Islam.  Kata Kunci: Demokrasi; Musyawarh; Pendidikan; Nilai.